KONTEKSTUALISASI MAKNA LA (JANGAN) DALAM QS.LUQMAN/31: 13 DALAM MENDIDIK ANAK - Sunardi Sunardi; Amrulah Harun (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2018)
Wikan Putri Larasati, M.Psi, from the Tangerang Castra Psychology Bureau, a pediatric psychologist, advised parents to avoid the word "no" or "no" when prohibiting children. The reason is, children have the potential to imitate saying "no" or "no" when asked to do something. In contrast to LuqmÄn al-Hakim who use the word do (lÄ) found in QS. Luqman / 31: 13 to signify the prohibition of associating partners with Allah Almighty. to his child. Of course this is contrary to what is stated by psychologists and parenting about the use of the word "do not" in educating children. This research method uses literature study which is presented in descriptive form. This study aims to harmonize the understanding of psychologists and parenting the use of the word "lÄ" in QS. Luqman / 31: 13 by using contextual understanding of verses. Based on studies of various literature, it can be concluded that the use of the word "do not" as stated by psychologists and parenting applies when the child is still in the process of knowing the definition of what is forbidden, while the use of the word "no" in QS. LuqmÄn / 31:13 applies to children who have been blessed or have known what is right and bÄtil. Keywords: Meanings of LÄ, Children, Contextual, QS. Luqman / 31:13